Antagonistic activity of probiotic strain of Lactobacillus against opportunistic bacteria during dysbiosis of intestine - Voronkova, Olga; Voronkova, Yu.S.; Vinnikov, Albert; Shevchenko , Tatiana (Problems of Environmental Biotechnology, 2021)
The aim of the research was to study the antagonistic properties of probiotic strain of Lactobacillus against opportunistic microorganisms isolated from the gastrointestinal tract of patients with dysbiosis. Isolated strain Lactobacillus spp. showed different effectiveness of antagonistic action against various opportunistic bacteria. The strain was significantly more effective against Gram-negative bacteria. The maximal antagonistic activity was observed against Escherichia coli and Proteus mirabilis. Strain was least effective against Staphylococcus aureus and Enterococcus spp.